Structural mechanisms for centrosomal recruitment and organization of the microtubule nucleator γ-TuRC - Gao, Qi; Hofer, Florian W.; Filbeck, Sebastian; Vermeulen, Bram J. A.; Würtz, Martin; Neuner, Annett; Kaplan, Charlotte; Zezlina, Maja; Sala, Cornelia; Shin, Hyesu; Gruss, Oliver J.; Schiebel, Elmar; et al. (Nature Communications, 2025)
The γ-tubulin ring complex (γ-TuRC) acts as a structural template for microtubule formation at centrosomes, associating with two main compartments: the pericentriolar material and the centriole lumen. In the pericentriolar material, the γ-TuRC is involved in microtubule organization, while the function of the centriole lumenal pool remains unclear. The conformational landscape of the γ-TuRC, which is crucial for its activity, and its centrosomal anchoring mechanisms, which determine γ-TuRC activity and turnover, are not understood. Using cryo-electron tomography, we analyze γ-TuRCs in human cells and purified centrosomes. Pericentriolar γ-TuRCs simultaneously associate with the essential adapter NEDD1 and the microcephaly protein CDK5RAP2. NEDD1 forms a tetrameric structure at the γ-TuRC base through interactions with four GCP3/MZT1 modules and GCP5/6-specific extensions, while multiple copies of CDK5RAP2 engage the γ-TuRC in two distinct binding patterns to promote γ-TuRC closure and activation. In the centriole lumen, the microtubule branching factor Augmin tethers a condensed cluster of γ-TuRCs to the centriole wall with defined directional orientation. Centriole-lumenal γ-TuRC-Augmin is protected from degradation during interphase and released in mitosis to aid chromosome alignment. This study provides a unique view on γ-TuRC structure and molecular organization at centrosomes and identifies an important cellular function of centriole-lumenal γ-TuRCs.
Gesehen am 12.08.2025